Application of Multivariate Calibration Methods, in Dissolution Testing and Simultaneous Determination of Atorvastatin and Ezetimibe in Their Combined Solid Dosage Form - Azin Jahangiri, Khosro Adibkia, Karim Asadpour-Zeynali, Yousef Javadzadeh, Hamed Hamishehkar, Mohammad Ba (Tabriz University of Medical Sciences, 2016)
Background: Two simple, precise and accurate multivariate calibration methods, partial least square (PLS) and principal component regression (PCR) have been applied for the simultaneous determination and dissolution profile evaluation of atorvastatin (ATV) and ezetimibe (EZT) in their binary mixtures and commercial tablets. Due to the closely overlapping spectral bands of the mentioned drugs, simultaneous determination without previous separation is not possible by conventional spectrophotometric methods. In the proposed methods (PLS and PCR) determination of chemicals was performed by the use of a full-spectrum multivariate calibration method. Methods: The experimental calibration matrix was designed orthogonally with 16 samples composed of different mixtures of both compounds in related mediums. The simultaneous determination of ATV and EZT was accomplished in mixtures through recording the absorption spectra within a range of 210 to 300 nm. Results: The concentration of ATV and EZT were considered in the linear range, between 8 to 14 µg.ml-1. The specificity of the methods was evaluated by analyzing laboratory prepared mixtures of the mentioned drugs in specific proportions. Conclusion: The applied methods were successfully employed in simultaneous spectrophotometric determination and dissolution profile evaluation of ATV and EZT in their prepared mixtures and pharmaceutical formulation.